Peran Literasi Digital dalam Memediasi Pengaruh Kompetensi Pegawai dan SIMRS terhadap Kinerja RSUD Dr. H. Abdul Moeloek Provinsi Lampung - Putra, Muhammad Ferdiansyah; Haninun, Haninun (Jurnal EMT KITA, 2026)
Healthcare is an essential component in ensuring the fulfillment of the community's need for quality medical services, where hospitals play a strategic role as institutions providing comprehensive and integrated healthcare services. This study aims to analyze the influence of employee competency and the Hospital Management Information System (SIMRS) on employee performance, both directly and indirectly through digital literacy as an intervening variable. The research approach used is descriptive quantitative. The results show that employee competency and SIMRS have a positive and significant effect on employee performance, and have a positive and significant effect on improving employee digital literacy. Digital literacy is proven to have a positive and significant effect on employee performance, while also mediating and strengthening the influence of competency and SIMRS on performance, where the influence of competency on performance is stronger when mediated by digital literacy compared to its direct influence. These findings confirm that digital literacy has a strategic role in optimizing the utilization of employee competency and the effectiveness of SIMRS implementation to improve employee performance sustainably. Therefore, the implications of this study emphasize the importance for hospital management to make employee competency development a strategic priority through continuous education and training programs, not only focusing on the technical aspects of health services, but also on increasing the ability to adapt to developments in information technology, so that digital literacy can become the main foundation in supporting digital transformation at Dr. H. Abdul Moeloek Regional General Hospital, Lampung Province.